THE ANTICIPATION OF EVIDENCE IN BRAZILIAN LABOR AND EMPLOYMENT PROCEDURAL LAW - Bruno Freire e Silva; Felipe Bernardes (Revista Eletrônica de Direito Processual, 2021)
The main purpose of this study is to analyze the anticipation of evidence (or “early production of evidence”) action in disputes between employers and employees within the Brazilian legal system. In order to achieve this goal, the paper provides a brief overview of the proceedings, as regulated by the Brazilian Code of Civil Procedure and analyses the jurists’ opinion on this topic. It also takes into account, when applicable, the regulation provided by Labor and Employment Procedural Law.